Rancang Bangun Pendidikan Multikultural Berdasarkan Kajian Teologi “Berbuat Baik” Menurut Perjanjian Lama - GP, Harianto (Basilius Eirene Press, 2022)
Doing good is universal in which all people with various religious, ethnic and other backgrounds are certainly happy to do good. The problems that arise in the following questions are: What are the values of doing good according to the Bible? What is the challenge of